Welcome to Mooseport - Petrie, Donald; Schulman, Tom; Iwanyk, Basil (Distributed by 20th Century, 2003)
A local plumber is plunged into the national spotlight when he takes on the former President of the United States, who can't believe he's running against the man installing his toilets. Whoever wins, one thing's for sure: this town isn't small enough for the both of them.